Decolonial Perspectives on Environmental Degradation and Yoruba Indigenous Religious Practice in Nigeria - Samuel Babalola; Goodness Ayokunle (Journal of Religion and Decoloniality, 2026)
Climate change and environmental degradation in southwestern Nigeria pose an existential threat to the ecological matrix at the heart of Yoruba indigenous religious practice, a knowledge system that colonial modernity has long marginalised, pathologised, and dispossessed. Trees and forests, rivers, and arable land are not merely material assets but sacred milieus, home to Orisa (deities) and ancestral spirits, constituting an indigenous cosmology that encodes centuries of ecological stewardship. This paper interrogates the compounding risks to foundational Yoruba religious life, including wood-carved shrines, iconographic sculptures, harvest-related offerings, and riverine rituals through a critical analysis of anthropogenic deforestation driven by extractive commercial timber economies, altered precipitative regimes (droughts and floods), and riverine pollution and desiccation. Drawing on recent empirical research and field surveys, this study documents the declining availability of high-quality hardwoods essential to shrine and sculptural production, the disruption of planting seasons by erratic rainfall, and the existential threats confronting river deities such as Osun as water volumes recede and pollution intensifies. Crucially, the paper centres indigenous responses as forms of decolonial agency: sacred groves and their associated taboos, long functioning as indigenous conservation mechanisms, are positioned here not as relics but as living epistemic resources threatened by colonial and postcolonial land-use regimes. The paper further engages contemporary cultural revitalisation efforts, including the UNESCO listing of the Osun-Osogbo grove as ambivalent sites where indigenous sovereignty and external institutional recognition converge and sometimes conflict. The paper argues that the sustainability of Yoruba religious and ecological life demands not merely technical conservation but the decolonisation of environmental governance itself, centring traditional ecological knowledge as an authoritative framework rather than a supplement to Western conservation paradigms.